Comparison of the penile microbiome in infant male circumcision: Mogen clamp versus Shangring - Salazar, Juan E; Park, Daniel E; Punjani, Nahid; Pham, Tony; Aziz, Maliha; Kigozi, Godfrey; Gray, Ronald H.; Kiboneka, Stephen D; Goldstein, Marc; Li, Philip S; Lee, Richard; Liu, Cindy M. (Elsevier B.V, 2024)
This study aimed to characterise the infant penile (coronal sulcus) microbiome and the effects of early infant male circumcision (EIMC), following a standard surgical method (Mogen Clamp) and a non-surgical alternative (ShangRing). We collected coronal sulcus swabs at baseline and on days 7 and 14 post-circumcision from infants assigned to receive EIMC by Mogen Clamp (n = 15) or ShangRing (n = 15), in a randomised trial in Rakai and Kakuuto, Uganda. We used 16S rRNA gene-based sequencing and broad-coverage qPCR to characterise the infant penile microbiome and assess the effects of EIMC in both study arms. Prior to EIMC, the infant penile microbiome had a mixture of facultative and strict anaerobes. In both study arms, EIMC caused penile microbiome proportional abundance changes characterised by decreases in penile anaerobes [ShangRing Prevotella: −15.0%, (SD = 19.1); Mogen clamp Prevotella: −3.6% (11.2); ShangRing Veillonella: −11.3% (17.2); Mogen clamp Veillonella: −2.6% (11.8)] and increases in skin-associated facultative anaerobes [ShangRing Corynebacterium: 24.9%, (22.4); Mogen clamp Corynebacterium: 4.7% (21.3); ShangRing Staphylococcus: 21.1% (20.5); Mogen clamp Staphylococcus: 18.1% (20.1)]. Clostridium tetani was not detected during the study. Mogen Clamp and ShangRing EIMC both changed the composition of the infant penile microbiome by reducing the proportional abundances of anaerobes and uropathogens, which is consistent with medical male circumcision findings in adults. C. tetani was not increased by either EIMC method. Bill and Melinda Gates Foundation.